Assessment of microplastic pollution in corals, seawater, and marine sediments in the Gulf of Thailand - Sutthacheep, Makamas; Chamchoy, Charernmee; Suebpala, Wichin; Wongnutpranont, Arirush; Jungrak, Laongdow; Aunkhongthong, Wiphawan; Pengsakun, Sittiporn; Klinthong, Wanlaya; Jowantha, Morakot; Sangsawang, Laddawan; Yeemin, Thamasak (Frontiers in Marine Science, 2025)
This study investigates the occurrence, abundance, and characteristics of microplastics (MPs) in coral reef ecosystems at two reef sites, Ko Khang Khao and Ko Ngam Yai, in the Gulf of Thailand. Coral, seawater, and sediment samples were analyzed to evaluate the spatial variability of microplastics in terms of their abundance, size distribution, shape, polymer composition, and color. MPs were detected in all coral samples, with concentrations ranging from 0.24 to 2.60 particles g-¹ w.w. Ko Khang Khao exhibited higher MP concentrations across coral species, with Pavona decussata, Pocillopora acuta, and Galaxea fascicularis showing the greatest accumulation. Statistically significant inter-site differences in MP abundance were observed in four coral species (p < 0.05). Coral surface was the dominant compartment for MP accumulation (63.05% at Ko Khang Khao and 61.82% at Ko Ngam Yai), followed by skeleton and tissue. MP size distribution varied by coral compartment, with coral skeletons retaining larger particles (>3000 µm) and tissues favoring smaller MPs (25–1500 µm). Fiber-shaped MPs were predominant across all sites and compartments. Polymer analysis revealed polyethylene terephthalate (PET) and polyethylene (PE) as the most common polymers, while notable amounts of polypropylene (PP), nylon, and polystyrene (PS) were also identified, indicating diverse anthropogenic sources. Color analysis showed blue MPs as the most abundant, followed by black, white/yellow, red, and green particles. Green MPs were notably absent at Ko Ngam Yai. In seawater, MP concentrations ranged from 0.88 to 1.61 particles m-³, with higher levels at Ko Khang Khao. Fiber was again the dominant shape, and PE and PET were the most common polymers. Sediment samples exhibited MP abundances ranging from 164.80 to 295.20 particles kg-¹, with Ko Khang Khao having a greater prevalence of smaller particles (<600 µm) and more diverse polymer types. Across all matrices, Ko Khang Khao consistently showed higher MP concentrations and greater diversity in MP characteristics compared to Ko Ngam Yai, likely reflecting greater anthropogenic influence. These findings emphasize the spatial heterogeneity of microplastic pollution in coral reef systems and underscore the need for localized management strategies to mitigate microplastic inputs in nearshore marine environments.